Healthy Bakery Composite Mixes - Nevskaya E.; Tyurina I.; Turina O.; Shulbaeva M.; Potapova M.; Golovacheva Y. (Техника и технология пищевых производств)
Introduction. Bread and bakery are products of mass consumption. However, bread can hardly be considered as a perfectly balanced healthy product. To improve the quality of bread and bakery products, it is necessary to develop new formulations of baking mixes that can improve the nutritional and biological value of the finished product. New varieties of healthier, better quality bread with high nutritional and biological value can improve the diet of the population. Study objects and methods. The present research featured baking mixes made up of the following components: wheat baking flour, wholemeal barley flour, wholemeal lentil flour, textured lentil flour, brown rice flour, buckwheat flour, wholemeal wheat flour, rye bakery flour, milk whey, and demineralized milk whey. The research employed generally accepted standard methods, as well as the quick dough method. Results and discussion. The shape stability of the bread was calculated as the ratio of its height to diameter. The research yielded five composite baking mixes: mix 1 – a diabetic mix with barley wholemeal flour; mix 2 – a diabetic mix with buckwheat flour and dry cheese whey; mix 3 – a diabetic mix with buckwheat flour and dry demineralized whey; mix 4 – a mix with lentil wholemeal flour and brown rice wholemeal flour; mix 5 – a mix with textured lentil flour and brown rice wholemeal flour. All five samples demonstrated satisfactory sensory, physical, and chemical quality indicators. The authors also determined nutritional value and percentage from the daily requirements of an adult diet. The results proved that the finished products had a high content of proteins, dietary fibers, and minerals. An analysis of the granulometric composition of the baking composite mixes showed that the particle size varied from 5 to 600 microns. The content of particles in the range from 10 to 50 microns was 30–35% of the total volume. There was no significant difference in the particle size distribution in the samples. The mixes were close to homogeneous, which makes it possible to predict the uniform distribution of prescription components in the storage process and the production of high-quality bakery products. Conclusions. The obtained characteristics of the developed mixes make it possible to introduce them into the existing technological schemes of bakery production without using special equipment for dosing and storage.